Routledge international handbook of qualitative nursing research - Beck, Cheryl Tatano (London : New York : Routledge, 2013)
"Qualitative research, once on the fringes, now plays a central part in advancing nursing and midwifery knowledge, contributing to the development of the evidence base for healthcare practice. Divided into four parts, this authoritative handbook contains over forty chapters on the state of the art and science of qualitative research in nursing. The first part begins by addressing the significance of qualitative inquiry to the development of nursing knowledge, and then goes on to explore in depth programs of qualitative nursing research. The second section focuses on a wide range of core qualitative methods, from descriptive phenomenology, through to formal grounded theory and to ethnography, and narrative research. The third section highlights key issues and controversies in contemporary qualitative nursing research, including discussion of ethical and political issues, evidence-based practice and Internet research. The final section takes a unique look at qualitative nursing research as it is practiced throughout the world with chapters on countries and regions from the UK and Europe, North America, Australasia, Latin America, to Japan, China, and Korea. With an international selection of established scholars contributing, this is an essential overview and will help to propel qualitative research in nursing well into the twenty-first century. It is an invaluable reference for all nursing researchers"--Provided by publisher.
pt. 1. What does qualitative nursing research do? -- pt. 2. Qualitative research methods -- pt. 3. Contemporary issues in qualitative nursing research methods -- pt. 4. International qualitative nursing research : state of the science.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nursing -- Research; Qualitative research; Electronic books